RANDOMISED DOUBLE-BLIND PLACEBO-CONTROLLED STUDY OF FOLIC ACID ADJUNCT FOR 8 WEEKS IN HYPERHOMOCYSTEINAEMIC HYPERTENSIVE PATIENTS IN ZARIA, NIGERIA - ONYEMELUKWE, Obiageli U; MAIHA, Bilkisu B; AYANWUYI, Lydia O; DAHIRU, Tukur (Journal of Drug Delivery and Therapeutics, 2018)
Objectives: This study was aimed at determining the effect of folic acid adjunct therapy on homocysteine (HCY) and blood pressure (BP) levels in hypertensive subjects.Method: The study was a double blind placebo-controlled trial on 100 hypertensive patients randomised into 50 folate and 50 placebo groups, where the folate group had 5 mg folic acid daily for 8 weeks. Fasting plasma homocysteine, folate and blood pressure levels were determined at baseline, at 4 and at 8 weeks. The Mixed Model Repeated Measures analysis of variance was applied for data analysis.Results: Hyperhomocysteinaemia was found at baseline in the folate (21.3 ± 5.7 µmol/L) and placebo (21.6 ± 4.9 µmol/L) groups which did not differ statistically (p > 0.05). Folic acid adjunct therapy, reduced homocysteine levels at 4 weeks by 2.0 µmol/L (9.2 %, p < 0.05) and at 8 weeks by 1.2 µmol/L (5.6 %, p < 0.05), with no significant (p > 0.05) systolic and diastolic blood pressure lowering effect. High base-line folate levels were found in both folate (113.8 ± 51.2 ng/ml) and placebo groups (109.5 ± 51.4 ng/ml) with no statistically significant difference (p > 0.05).Conclusion: Short-term daily folic acid supplementation over 8 weeks had a significant homocysteine reduction effect with no significant reduction in systolic and diastolic blood pressures of hypertensive subjects in Zaria, Nigeria. Hyperhomocysteinaemia could not be accounted for by suboptimal folate levels.Keywords: Hypertension, Homocysteine, Blood pressure, Folate, Placebo, Nigeria.